Hegel and the beautiful soul. Ethical and political considerations from the Phenomenology of Spirit - Vega C., Francisco (Nómadas. Critical Journal of Social and Juridical Science, 2011)
This paper will attempt to address the problem that (after a systematic historical review) governs the interpretive horizon of Hegel’s philosophy about the movements illustrated. This is the foundation of a new national culture and the establishment of a real political effectiveness of thought. To do this, we juxtapose some Hegelian texts and compare final passages of the Phenomenology of spirit in with other attempts of tacit political resolution. We will analyze specifically the problem of Hegel’s interpretation of the Enlightenment and the beautiful soul.